Persilangan dan karakterisasi drosophila melanogaster strain normal dengan strain white - Ilmiyah, Alifa (Maliki Interdisciplinary Journal, 2025)
Drosophila melanogaster, commonly known as the fruit fly, is a widely used model organism in genetic research due to its short life cycle, ease of maintenance, high fertility, small body size, and relatively simple genetic structure that is easy to observe. One of its main advantages is the presence of clear phenotypic variations, such as eye color, making it highly suitable for studying inheritance patterns based on Mendel’s laws. This study aimed to cross Drosophila melanogaster with normal red eyes and the white-eyed strain under Mendel’s First Law, in order to understand inheritance principles, detect mutations, and examine the genetic mechanisms regulating phenotypic expression. The experimental method involved crossing male and female flies of both strains, followed by rearing and observing the F1 and F2 offspring at the imago stage. Crosses produced F1 offspring with 100% red eyes (genotype Nn). In the F2 generation, the phenotypic ratio was 3 red-eyed to 1 white-eyed, with a genotypic ratio of 1 NN : 2 Nn : 1 nn. These results confirm Mendel’s law of segregation, showing that the red-eye allele is dominant over the white-eye allele.